Papillary meningioma: a rare but distinct variant of malignant meningioma - Shruti Sharma; Vermani Sarvjot; Avninder Singh; Chand Karam (BMC, 2007)
Abstract Background Papillary meningiomas are rare meningeal tumors and are associated with aggressive clinical behavior as compared with other meningiomas. Because of their rare occurrence, they may pose a diagnostic dilemma to the unwary pathologist. We report a case of papillary meningioma in a 16-year-old boy. Case Presentation A 16-year-old boy presented with complaints of headache, progressively diminishing vision and more recently generalized seizures. MRI revealed a large bifrontal meningioma which showed presence of a predominantly papillary pattern with areas of focal necrosis, frequent mitoses and bone invasion. He underwent radical excision of the tumor and is free from recurrence or metastasis at 15 months follow-up. Conclusion Papillary meningiomas are rare but well recognized variants of meningioma. They need to be differentiated from other intracranial tumors with a papillary pattern. They are malignant, frequently show bone and parenchymatous invasion and have the potential for extracranial metastasis. Their timely recognition could prevent local and distant metastasis and the mortality or morbidity associated with it.